Violence in Jamaica’s high schools - Grant, Lorna Elaine (African journal of criminology and justice studies, 2017)
This research determines the presence of crime, the disciplinary policies and procedures, and security measures on high school campuses in Jamaica. Data was collected from 27 randomly selected public high schools in the parishes of Kingston, St Andrew and St. Catherine through the administration of interviews, self-reported questionnaires and focus group discussions. School administrators (principals), teachers, guidance counselors and resource officers were engaged in face to face interviews. Male students (n=405), ages 12 to 17 years old who were classified as disruptive students, were randomly selected from lists provided by principals and school guidance counselors to participate in the research. Data was analyzed using qualitative research data management software programs, including Atlas-Ti version 4.2. and the Statistical Package for the Social Sciences (SPSS Version 15) software. Violence occurred because of: (a) administrators’ denial of school violence on their school campus, (b) non-caring school environment, and (c) poor implementation of school policies coupled with inadequate school security.. Violence on high school campuses in Jamaica mirrors the violence in the wider society; and school administrators often ignore or downplay the seriousness of violence in their schools. High schools in Jamaica fall into two categories: public and private. The public high schools are further categorized as Traditional and Non-Traditional High Schools. The better performing students in the GSAT examination usually go to the Traditional High School and the excellent performers among these are awarded various scholarships in the highly recognized high schools. Lower performing students are placed in the Non-Traditional High Schools. This research is focuses on Traditional High Schools that are public funded.